2018
DOI: 10.1038/s41612-018-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

Does elevation-dependent warming hold true above 5000 m elevation? Lessons from the Tibetan Plateau

Abstract: Available observations below 5000 m altitude suggest that some mountain regions are undergoing accelerated elevationdependent warming (EDW) in response to global or regional climate change. We address the question of whether EDW exists above 5000 m altitude, which is the elevation of much of the mountainous portion of the Tibetan Plateau, and headwaters to most of Asia's major rivers. We analyzed four data sources: in situ observations, gridded observations, ERA-Interim reanalysis, and Weather Research and For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 33 publications
8
79
0
Order By: Relevance
“…Enhanced warming is not observed at extreme high elevations above 6,000 m. Indeed, a reversal and even absolute cooling trend is seen in the LST data (both raw and corrected) above 6,000 m and especially around 7,000‐7,500 m. Thus warming at the very least may stabilize at the very highest elevations. This has been suggested by other studies on the plateau based on satellite observations (Qin et al, ) and through modeling (Gao et al, ; Guo et al, ). The latter study uses Weather Research and Forecasting simulations and projects future warming rates under Representative Concentration Pathways 4.5/8.5 to peak around 5,000 m and slowly decrease above this.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Enhanced warming is not observed at extreme high elevations above 6,000 m. Indeed, a reversal and even absolute cooling trend is seen in the LST data (both raw and corrected) above 6,000 m and especially around 7,000‐7,500 m. Thus warming at the very least may stabilize at the very highest elevations. This has been suggested by other studies on the plateau based on satellite observations (Qin et al, ) and through modeling (Gao et al, ; Guo et al, ). The latter study uses Weather Research and Forecasting simulations and projects future warming rates under Representative Concentration Pathways 4.5/8.5 to peak around 5,000 m and slowly decrease above this.…”
Section: Discussionsupporting
confidence: 69%
“…We compare trend patterns in raw and corrected LST with air temperature trends at the stations. While several studies have attempted to obtain an EDW profile on the plateau‐wide scale (e.g., Gao et al, ; Qin et al, ), this approach can hide important regional differences in profiles of warming, and therefore the mechanisms responsible. The plateau covers a wide area and includes a range of climates, from monsoonal dominated regions in the south and east to continental areas in the north, and westerly dominated regimes in the far west.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al . () used model simulations to examine future (21st century) patterns of elevation‐dependent warming, and projected peak warming around 5,000 m associated with snow‐albedo feedback, and a decrease above this elevation. Guo et al .…”
Section: Discussionmentioning
confidence: 99%
“…predicted maximum warming rates around 4,400-5,200 m based on high-resolution dynamical downscaling simulations. Gao et al (2018a) used model simulations to examine future (21st century) patterns of elevation-dependent warming, and projected peak warming around 5,000 m associated with snowalbedo feedback, and a decrease above this elevation. Guo et al (2019) used SBAT to reveal a reversal in elevation dependent warming above 4,500 m on the TP in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Guo and Wang (2012) point out that there was no EDW in the northern Tibetan Plateau, and other areas in the Tibetan Plateau have EDW from 1961 to 2007. Gao et al (2018) showed that Tibetan Plateau has EDW below 5000 m, while no EDW occurred above 5000 m during the period from 1983 to 2011. However, other studies suggested that there was no obvious relationship between trend magnitude of air temperature and elevation (Vuille et al 2003, Pepin and Norris 2005, You et al 2008, Yang et al 2012, Li et al 2013.…”
Section: Introductionmentioning
confidence: 99%